Investigating thermal conditions in a tropic atrium employing CFD and DTM techniques - Fan Wang, Fan Wang; Abdullah, Abd Halid (Oxford University Press, 2011)
Focusing on the ‘worst-case scenario’, a modelling study was carried out to examine whether a low cost ventilation solution could provide basic comfort in a specific atrium-building design. This study combined dynamic thermal modelling (DTM) and computational fluid dynamics (CFD) in investigating how thermal conditions, namely the air movement and temperature distribution within an atrium responded to the side-lit form and other changes of design variables such as inlet to outlet opening area ratios and also the outlet’s arrangement. The predicted temperature distribution, airflow patterns and comfort indices would provide a better understanding how the design variables affect thermal condition and comfort within the atrium, particularly at the occupied areas under a low cost ventilation solution—pressurized ventilation. The simulation results revealed that sufficiently higher inlet to outlet opening area ratio (i.e. n . 1) could improve the thermal condition on the open corridors, the occupied areas, even on high levels; while with an equal inlet to outlet opening area ratio (i.e. n ¼ 1), changing the outlet’s arrangement (i.e. location and configuration) did not significantly affect thermal condition. The practical aspect of this study is 2-fold. First, the low cost ventilation solution using exhaust air from surrounding fully air-conditioned rooms could provide acceptable thermal comfort at the open corridors/walkways surrounding the atrium. Secondly, combining a DTM and CFD can be an effective tool to test various design options to achieve an optimal solution. The parametric presented here could be used in similar studies aiming at optimize environmental engineering solutions that balance comfort and cost.